NILAI NILAI PENDIDIKAN DI DALAM SURAT AL-FATIHAH - fauzi, fauzi caniago (TEXTURA, 2022)
Understanding the meaning of Islamic education in the Qur’an means having to analyze pedagogically a main aspect of the Qur’an as a guide for Muslims containing educational implications that are able to guide and direct humans to become a believer, Muslim, muhsin, and mutakin through a step-by-step process. Almost two-thirds of the verses of the Qur’an contain educational motivation for mankind. The purpose of this study is to find out the educational values ​​contained in the letter Al-Fatihah, to know the concept of education in the letter Al-Fatihah, to find out the method of education in the letter Al-Fatihah. This research is a library research (library research). Where the data is obtained from library sources in the form of books related to the subject of research, the research data is collected by the documentation method. A literature review is carried out to explore concepts, theories, data from various existing literature sources and then used as a framework in viewing and assessing the objective conditions of various problems that occur in the field. The values ​​listed in Surah Al-Fatihah are. I) Value of Faith, 2) Value of Worship Education, 3) Value of Education on Islamic Law, 4) Educational Value of Stories (Exemplary).